The Outcomes of Percutaneous Coronary Intervention in Chronic Total Coronary Occlusion: A Single Center Report - Rahman, AKM Fazlur; Salman, Mohammad; Banerjee, Sajal K; Anam, Khairul; Rahman, Mukhlesur; Ahmed, Md Khurshed; Zaman, SM Mustafa; Habib, Ahsan; Siddique, Md Abu; Haque, KMHS Sirajul; et al. (University Heart Journal, 2011)
Chronic total occlusions (CTOs) are commonly found on diagnostic angiography, and successful percutaneous coronary intervention leads to an improvement in long-term survival rates. This study was done in the University Cardiac Center, Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2005 to December 2009. The aim of this study was to examine the trends in angiographic success, clinical success, procedural success and in-hospital outcomes after percutaneous coronary intervention (PCI) for chronic total occlusions (CTO). Total 60 patients (male: female, 11:1) with Mean age 48±10 years were studied. 36 (60%) patients had prior myocardial infarction and all of them had angina (CCS-III, IV). Mean length and reference diameter of the CTO lesion was 19.7±10.4 mm and 2.8±0.5 mm respectably. Clinical success, angiographic success and procedural success rate was (78.3%), (80.0%) and (66.7%) respectably. In hospital adverse outcomes were acute myocardial infarction (5.0%), acute left ventricular failure (6.7%) and malignant arrhythmias (VT, VF) (10.0%). PCI was failed in (11.7%) cases and there was acute in-stent thrombosis in (1.7%) cases. In conclusion it is possible to obtain a relatively high success rate of PCI and favorable clinical outcomes for patients with coronary CTO lesions. Key words: Chronic total occlusions; In hospital adverse outcomes; Percutaneous coronary intervention DOI: 10.3329/uhj.v6i1.7183 University Heart Journal Vol.6(1) 2010 pp.13-17